2017
DOI: 10.1016/j.jceh.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cerebral Edema in Acute-on-Chronic Liver Failure

Abstract: Cerebral edema increases with severity of ACLF. Correlation between MD values and IL-6 levels suggests pathogenic role of inflammation in cerebral edema. Patients with grade 3 ACLF have cerebral edema irrespective of presence of clinically evident cerebral failure. MELD score and cerebral edema have prognostic significance in ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The presence of HE itself increases short-term mortality in ACLF as is the severity, i.e., grade of HE [3]. The pathophysiology of HE is complex, and impairment of brain energy and development of brain edema appear to be central in the pathogenesis of encephalopathy [117,118]. Inflammation plays a greater role in the pathogenesis of HE in patients with ACLF than in patients without ACLF and is associated with a cytokine storm.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of HE itself increases short-term mortality in ACLF as is the severity, i.e., grade of HE [3]. The pathophysiology of HE is complex, and impairment of brain energy and development of brain edema appear to be central in the pathogenesis of encephalopathy [117,118]. Inflammation plays a greater role in the pathogenesis of HE in patients with ACLF than in patients without ACLF and is associated with a cytokine storm.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%
“…Cerebral edema has been observed in ACLF, and even low cerebral edema can be detected by proper CT and MRI. Vasogenic cerebral edema as detected by advanced MRI techniques like magnetization transfer ratio (MTR), diffusion tensor imaging (DTI) and diffusion weighted imaging (DWI) is common, but rarely requires specific treatment [118]. Using advanced MRI techniques, Gupta et al demonstrated presence of cerebral edema increases with severity of ACLF.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%
See 1 more Smart Citation
“…HE in acute liver failure is a distinct type of HE that occurs in the context of severe cytokine storm and brain as well systemic hemodynamic alteration (21,22); thus, it has separate features in which brain swelling and intracranial hypertension have a peculiar role, thus it is a distinct condition with respect of HE occurring in cirrhosis and in non-cirrhotic portal systemic shunts (8). Recently it has been observed that HE in acute on chronic liver failure has some peculiar features (23,24). It frequently occurs in the context of multiorgan failure, sepsis and cytokine storm that reasonably produce overlapping metabolic/haemodynamic encephalopathies that may deserve to be considered separately and frequently require multitarget treatment in ICU managed patients.…”
Section: The Meaning Of the Term Hementioning
confidence: 99%
“…Recently, it was proposed that a distinction be made between patients with and without acute‐on‐chronic liver failure (ACLF) . The main reason for this is the more severe prognostic value of HE in the context of ACLF, the finding that intercellular brain oedema is parallel with the degree of HE, and, in rare reports, of intracranial hypertension . Cases of ACLF are characterised by greater inflammation than in patients without ACLF, which damages the brain–blood barrier, as well as other injuries to the brain due to multiorgan failure and drug treatments .…”
Section: Diagnosis and Classification Of Hepatic Encephalopathymentioning
confidence: 99%